Basic Research of the Perception of Corporate Social Responsibility in the Academic Environment - Vartiak, Lukas (International Journal of Business, Law, and Education, 2025)
Corporate Social Responsibility (CSR) has traditionally been associated with the private sector, focusing on ethical business practices, environmental sustainability, and community engagement. Despite its growing importance, CSR in academia remains underexplored, lacking comprehensive methodologies for measuring and evaluating its impact. This research investigates the perception and implementation of CSR in the academic environment, aiming to propose a framework model for its strategic integration into universities. The research incorporates quantitative data from questionnaire surveys conducted at selected European universities and qualitative insights from in-depth interviews with university management, faculty, and administrative staff. The findings indicate that while awareness of CSR is relatively high, there is a significant gap between knowledge and implementation. A four-step CSR implementation model is proposed to address these challenges, emphasising strategic management, financial sustainability, stakeholder engagement, and continuous evaluation. Future research should focus on developing standardised CSR metrics and assessing the long-term effects of CSR in academia.